Giant fibrosarcoma of anterior abdominal wall: a rare case report and review literature - Vishnoi, Jeewan Ram; Kori, Channabasappa; Shukla, Saumya; Gupta, Sameer; Kumar, Vijay; Rajan, Shiv (International Journal of Research in Medical Sciences, 2017)
Adult type fibrosarcoma is very rare malignant soft tissue tumor. It usually arises in soft tissues of extremities, trunk, head and neck. Fibrosarcoma is essentially a diagnosis of exclusion from other spindle cell mesenchymal malignant neoplasm; by definition negative for epithelial, myogenous and neural markers on immunohistochemistry. To the best of our knowledge, very few cases have been reported in the literature. We here report a case of giant fibrosarcoma arising from anterior abdominal wall in a recurrent dermatofibrosarcoma proturbens and managed with surgical excision and reconstruction with meshplasty.